The Impact of Learners' Autonomy on EFL Learners' Reading Comprehension: The Case of Second Year Students of English at Souk-Ahras University - HARIRECHE Riheb (My University, 2022)
Abstract Reading comprehension requires certain skills and abilities including learning autonomy. This latter has become a popular concept due to its importance in the learning process. For this reason, this study seeks to highlight the impact and the importance of learning autonomy on enhancing EFL learners' reading comprehension through conducting two questionnaires for both EFL teachers and EFL second year students at Mohamed Cherif Messaadia in Souk Ahras. The main concern of the current study is that EFL learners lack reading comprehension. Therefore, the work attempts to look for ways to promote learners' autonomy, and to investigate the problems that may face the EFL learners during reading class. The findings revealed the positive impact of learner autonomy on enhancing learners' reading comprehension. It also demonstrated that EFL learners face a plenty of difficulties during reading class.